Gamification in English Language Learning for Seafarers in Preparation for Marlins Test: Enhancing Motivation and Engagement - Yuliana Fatima Dayana; Laila Puspitasari Anggraini; Capt. Suhartini; Aliya Izet Begovic Yahya (Didaktika: Jurnal Kependidikan, 2025)
This study explores the impact of gamification on motivation and engagement in English language learning among seafarers preparing for the Marlins test. Employing a mixed-methods approach, quantitative surveys and qualitative interviews were conducted to investigate the effects of gamification. The theoretical framework integrates gamification principles and Self-Determination Theory to examine how game-like elements enhance intrinsic motivation and learning outcomes. Results indicate that gamification fosters engagement by providing clear goals, immediate feedback, and a sense of achievement. The findings suggest practical implications for maritime education in creating autonomous learning environments that sustain motivation and enhance language proficiency.